The Impact of financial development on poverty alleviation in Sub-Saharan Africa - MANYANI, Talent Khayelihle (KDI School, 2015)
Around 80% of the Sub-Saharan African population lives below the $2 a day poverty line, under miserable conditions because of armed conflicts, and bad governance. By using private credit as a measure of financial development and the poverty gap, as a proxy for poverty, this paper studies the impacts of financial sector development on poverty. This paper employs the panel data econometric analysis and the results suggest that financial development can contribute to poverty alleviation in Sub-Saharan Africa.
Thesis(Master) --KDI School:Master of Development Policy,2015